Biological effects of curcumin-loaded PLGA nanoparticle conjugated with anti-p-glycoprotein antibody on multidrug resistant cancer cells in vitro and in animal models - Wanisa Punfa (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Curcumin (Cur), a phenolic compound purified from the rhizome of Curcuma longa, has been reported to reduce both expression and function of P-glycoprotein (P-gp), a drug efflux pump. However, low level of oral bioavailability, poor absorption ability, a high metabolic rate, poor pharmacokinetics and solubility are the limitation of the research and development in terms of using Cur in clinical applications. Therefore, we then have tried to develop the drug delivery system using nanotechnology for entrapment of Cur in polylactic-co-glycolic acid (PLGA) nanoparticles (Cur-NPs) to improve its solubility and stability. Moreover, conjugation of the Cur-NPs with anti-P-gp antibody (Cur-NPs-APgp) might increase specificity of the conjugated nanoparticles (NPs) to P-gp. This study, we determined whether Cur-NPs-APgp could enhance cellular uptake, increase cytotoxicity and increase paclitaxel (PTX) sensitivity in human multidrug resistant cervical carcinoma (KB-V1) cells to overcome MDR in vitro and in vivo. Cur was entrapped into PLGA nanoparticles in the presence of modified-pluronic F127 stabilizer using nanoprecipitation technique. On the surface of Cur-NPs, the carboxy-terminal of modified pluronic F127 was conjugated to the amino-terminal of anti-P-glycoprotein using carbodiimide reaction. After that, the physical properties and biological activities of the NPs were investigated. The NPs fabrication showed smooth and spherical particle having the particle sizes of 127 and 132 nm for Cur-NPs and Cur-NPs-APgp, respectively. These particle sizes are suitable for use in drug delivery system. The polydispersity index (PDI) of the NPs exhibited narrow size distribution. The percent entrapment efficiency and actual loading of Cur-NPs-APgp (60% and 5 µg Cur/mg NP) were lower than those of Cur-NPs (99% and 7 µg Cur/mg NP). The constructed NPs showed similar sizes indicating their stability in various solutions at different time. The specific binding of Cur-NPs-APgp to KB-V1 cells (higher expression of P-gp) was significantly higher than that to KB-3-1 (lower expression of P-gp) cells. Cellular uptake of Cur-NPs-APgp into KB-V1 cells was higher than in KB-3-1 cells whereas the cellular uptake of Cur-NPs and Cur-NPs-IgG had no difference between the cell lines. Besides, the cytotoxicity of Cur-NPs-APgp in KB-V1 cells was higher than those of Cur- and Cur-NPs-treated cells. The combined treatment of PTX with Cur obviously decreased cell viability and tumor growth when compared with the treatment of PTX alone. In animal studies, Cur-NPs-APgp and Cur-NPs could be detected in the serum at up to 60 and 120 min, respectively after intravenous injection, whereas Cur was not detected after 30 min. The pre-treatment of Cur-NPs-APgp but not NPs and Cur-NPs followed by PTX, could enhance PTX sensitivity both in vitro and in vivo leading to induce cell death in KB-V1 treated cells and decreased tumor growth in KB-V1 xenograft model. The pre-treatment of NPs-APgp followed by PTX also enhanced PTX sensitivity to KB-V1 cells but the effect was lower compared to the pre-treatment of Cur-NPs-APgp followed by PTX treatment. In conclusion, our functional Cur-NPs-APgp might be a suitable candidate for applications in the drug delivery system. The further development of Cur-NPs-APgp may be beneficial for cancer patients, either as a MDR modulator or as an anti-cancer drug. Besides, the NPs-APgp might be an alternative carrier for the entrapment of anticancer drugs, which are substrates of the P-gp.